Bridging Work and Family Life: The Role of Work Engagement in Optimizing Job Crafting at Bringkoning Health Center: - mufidah, Mumilatul; Jaelani , Abdul Qodir; Mardani , Ronny Malavia (Journal of Business and Management Review, 2025)
Research Aims: The aim of this research is to analyze the role of work engagement in mediating the relationship between job crafting and work family enrichment. The population selected in this study were employees of UPTD PUSKESMAS Bringkoning, Banyuates District, Sampang Regency. Design/methodology/approach: The sampling technique used is purposive sampling, namely taking sample members from the population by determining certain criteria. The sample from this research were employees of UPTD PUSKESMAS Bringkoning, Banyuates District, Sampang Regency, who were 36 permanent employees. The data analysis method uses partial least squares (PLS). Research Findings: The results of this research prove that there is a direct influence of job crafting , work engagement on work family enrichment and there is an indirect influence of job crafting on work family enrichment and work engagement is able to mediate the relationship between job crafting and work family enrichment for employees of UPTD PUSKESMAS Bringkoning, Banyuates District, Sampang Regency. However, the direct relationship is higher when compared to the indirect influence Theoretical Contribution/Originality: By bridging these concepts, this research explores a deeper understanding of how changes in an individual's work can have a positive impact on their family life. The integration of the concepts of job crafting and work-family enrichment, especially in the context of health services, provides new insights into the dynamics of the relationship between work and personal life. The findings of this research have significant implications for human resource management in developing policies and practices that support employee well-being and balance between work life and family life.